Analysis of Pin Fin Shapes on Thermal Performances in Microchannel Heat Sink using Computational Fluid Dynamics (CFD) - Muhammad Hazwan Ruhaidi,; Nofrizalidris Darlis, (Progress in Engineering Application and Technology, 2025)
As technology continues to miniaturize, efficient thermal management remains a critical challenge, particularly in applications involving electronic devices such as CPUs and integrated circuits. Microchannel heat sinks (MCHS) have emerged as a prominent solution, yet their thermal performance can still be optimized. This study investigates the impact of different triangular, square, and hexagonal pin fin geometries on the thermal performance of MCHS using computational fluid dynamics (CFD) simulations in ANSYS Fluent. The analysis focuses on key thermal parameters, including maximum temperature, pressure drop, and temperature contour, across a range of Reynolds numbers (200–1000). Results indicate that square-shaped pin fins demonstrate superior thermal performance by achieving the lowest maximum temperature which is 316.512 K, while circular pin fins exhibit the least pressure drop. However, the square-shaped geometry also incurs a higher pressure drop, highlighting the trade-off between thermal efficiency and fluid flow resistance. The findings provide valuable insights for optimizing microchannel heat sink designs and enhancing cooling efficiency in high-performance electronic systems.